The choreography of everyday life - Parson, Annie-B (Verso, 2022)
"In this sparkling, innovative, fully illustrated work, world-renowned choreographer Annie-B Parson translates the components of dance-time, proximity, space, motion, and tone- into text. Parson invites the reader to share her home, her reading, her walks down the street, and her conversations on everything from Homer to feminist art to social protest. She helps us to see how everyday movement creates the wider world. Dance, it turns out, is everything and everywhere"--